2017
DOI: 10.1175/jcli-d-16-0467.1
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Arctic Oscillation and Diversity of the Extreme Surface Weather Anomalies It Generates

Abstract: Through a cluster analysis of daily NCEP–NCAR reanalysis data, this study demonstrates that the Arctic Oscillation (AO), defined as the leading empirical orthogonal function (EOF) of 250-hPa geopotential height anomalies, is not a unique pattern but a continuum that can be well approximated by five discrete, representative AO-like patterns. These AO-like patterns grow simultaneously from disturbances in the North Pacific, the North Atlantic, and the Arctic, and both the feedback from the high-frequency eddies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The correlation coefficient between the May−July AO and the persistence of the positive EWD pattern was -0.45, which is statistically significant at the 95% confidence level. The AO is a primary mode of atmospheric variability over the extratropics of the Northern Hemisphere, and is significantly connected to the atmospheric circulations over the mid-to-lower latitudes (Park et al 2011, Dai & Tan 2017. indicated that the influence of the spring AO on the following East Asian summer monsoon became obvious and significant during the mid-1970s to mid-1990s.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficient between the May−July AO and the persistence of the positive EWD pattern was -0.45, which is statistically significant at the 95% confidence level. The AO is a primary mode of atmospheric variability over the extratropics of the Northern Hemisphere, and is significantly connected to the atmospheric circulations over the mid-to-lower latitudes (Park et al 2011, Dai & Tan 2017. indicated that the influence of the spring AO on the following East Asian summer monsoon became obvious and significant during the mid-1970s to mid-1990s.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of phenomena have been proposed as potential sources of predictability for the winter AO, with time scales of seasons to decades (e.g., Smith et al, 2016). Among other factors, AO skill could arise from tropical climate anomalies, including ENSO (Dai & Tan, 2017;Dunstone et al, 2016;Tang et al, 2007;Yu & Lin, 2016), as well as Arctic sea ice (Wang et al, 2017), Eurasian snow cover (Cohen et al, 2010), and stratospheric-tropospheric coupling (Butler et al, 2016;Sigmond et al, 2013). Whatever mechanisms are responsible for AO skill, it would seem that only now have state-of-the-art forecasting systems been able to represent them with sufficient accuracy, either through improved physics, better data assimilation, or improved observing networks.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the case of heat waves, strong geopotential anomalies were observed in the upper parts of the troposphere, although they were positive (Chen et al, ; Tomczyk et al, , ). Analysing the upper troposphere, disturbances were found useful in following the process of the Arctic Oscillation's formation and propagation (Dai and Tan, ). Tomassini et al () related the extreme winter cold spells over Northern Europe to preceding circulation anomalies in the stratosphere (weakening in the stratospheric polar vortex); several cold spells occurred in association with a downward propagating dynamical disturbance which originated in the stratosphere.…”
Section: Discussion and Summarymentioning
confidence: 99%